Experiência do Usuário de Longo Prazo Em Plataforma de Software Crowdsourcing - Assmann, Márcia Prante; Zanatta, Alexandre Lazaretti; De Marchi, Ana Carolina B. (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2021: Anais do XX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2021)
The development of crowdsourcing software is commonly organized around platforms that allow a requester to submit a task and connect it with a crowd of individuals, who will provide likely solutions to the task. However, these platforms often ignore factors that provide a satisfactory user experience, reflecting, among others, the abandonment of tasks. To this end, it is essential to identify and understand User Experiences (UX) on platforms, assist in the improvement/development of these environments, and minimize barriers imposed by unsatisfactory experiences problems. This paper aimed to investigate long-term UX on a crowdsourcing platform. It is a qualitative exploratory study, carried out from a quasi-experiment, in which 10 undergraduate students selected for convenience participated. Participants performed tasks on the TopCoder platform over 3 months and answered the online questionnaire. Throughout the period, participants reported their experiences with the platform, describing their impressions about the use. The results showed the most satisfactory experiences occurred mainly in the last weeks of study and were mainly associated with the completion and task submission. For less satisfactory experiences, the main reasons identified were mainly associated with the difficulty of use and low usability. All participants informed that they would recommend the platform to others. It is concluded that, even with usability problems, the user’s experience when using the platform was satisfactory. The results can be used to suggest mechanisms that reduce the barriers imposed by problems of less satisfactory experiences, spreading the crowdsourcing software and, consequently, expanding its adoption in the software development industry.